Sex differences in gene expression and proliferation are dependent on the epigenetic modifier HP1γ - Law,P-P; Chan,P-K; McEwen,K; Zhi,H; Liang,B; Naruse,C; Asano,M; Tan-Un,K-C; Chan,GC-F; Festenstein,R (BioRxiv, 2022)
Summary Sex differences in growth rate in very early embryos have been recognized in a variety of mammals and attributed to sex-chromosome complement effects as they occur before overt sexual differentiation. We previously found that sex-chromosome complement, rather than sex hormones regulates heterochromatin-mediated silencing of a transgene and autosomal gene expression in mice. Here, sex dimorphism in proliferation was investigated. We confirm that male embryonic fibroblasts proliferate faster than female fibroblasts and show that this proliferation advantage is completely dependent upon heterochromatin protein 1 gamma (HP1γ). To determine whether this sex-regulatory effect of HP1γ was a more general phenomenon, we performed RNA sequencing on MEFs derived from males and females, with or without HP1γ. Strikingly, HP1γ was found to be crucial for regulating nearly all sexually dimorphic autosomal gene expression because deletion of the HP1γ gene in males abolished sex differences in autosomal gene expression. The identification of a key epigenetic modifier as central in defining gene expression differences between males and females has important implications for understanding physiological sex differences and sex bias in disease.